UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN PALA (Myristica fragrans Houtt) TERHADAP Staphylococcus epidermidis - Wandan Wisdyafanny, Marcelina; Silviani, Yusianti (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2023)
Acne vulgaris or acne can be caused by bacteria, one of them is Staphylococcus epidermidis which will produce lipolytic enzymes that turn sebum into a solid mass, then it will clog the ducts of the sebaceous glands. Nutmeg leaves contain saponins, triterpenoids, tannins, and flavonoids used as an antibacterial. The purpose of this study was to determine the inhibition of the ethanol extract of nutmeg (Myristica fragrans Houtt) leaves on the growth of Staphylococcus epidermidis. This study used a descriptive experimental research method to determine the antibacterial effectiveness of the ethanol extract of nutmeg (Myristica fragrans Houtt) leaves against Staphylococcus epidermidis. The data source for this study was primary data based on the results of the inhibition zone on Staphylococcus epidermidis by administering ethanol extract of nutmeg (Myristica fragrans Houtt) with concentrations of 20%, 40%, 60%, 80%, and 100%. The results showed that the ethanol extract of nutmeg leaves could be used as an antibacterial against Staphylococcus epidermidis. The average diameter of the inhibition zone of nutmeg leaf extract formed at 20% concentration was 10,45 mm, at 40% concentration was 11,4 mm, at 60% concentration was 11,9 mm, at 80% concentration was 12,35 mm, and at a concentration of 100% that is equal to 12,6 mm. The concentration of 100% was able to inhibit Staphylococcus epidermidis with the widest average diameter of the inhibition zone, which was 12,6 mm.